The mist - Ragnar Jónasson, 1976- (Hidden Iceland series, 2020)
"The final nail-biting installment in Ragnar Jonasson's critically-acclaimed Hidden Iceland series, The Mist, from the newest superstar on the Icelandic crime fiction scene. 1987. An isolated farm house in the east of Iceland. The snowstorm should have shut everybody out. But it didn't. The couple should never have let him in. But they did. An unexpected guest, a liar, a killer. Not all will survive the night. And Detective Hulda will be haunted forever"--